Research on the Structural Strength of the New Energy Cantilever Type Reducer Box at the Wheel Side - Huang Hongtao; Xu Wenbo; Zhong Ming; Wang Xiaopeng; Sun Jiang (Jixie chuandong)
The wheel reducer is one of important transmission structures of heavy or new energy vehicles for increased torque and reduces speed. The gearbox mainly carries the internal load from gear transmission and the external load from frame connection. The reasonable design and strength performance of the gearbox are important guarantees for the smooth operation of the wheel reducer. Based on the three-dimensional geometric structure of the gearbox and the finite element analysis method, a structural strength analysis method integrating "model-strength evaluation-running" is established and the structural strength of the gearbox is investigated comprehensively. The results show that the box under the load and strength evaluation criteria of combined calculation has sufficient design strength and stiffness, which can support the smooth operation of the infield transmission system and resist the deformation caused by external load. The distributed contact area of the joint surface of gearboxes is ensured by the sufficient distribution and strength of bolts, and no oil leakage occurs in the gearbox. The operational experiment result of gearboxes is in agreement with the above theoretical analysis. The proposed structural strength analysis method provides a technical basis for the structural design of the gearbox.